Metaplastic carcinoma of breast: Case series with cytohistological correlation - Neelam Sood; Sanjay Gupta; Soin Navmeet (Indian Journal of Medical and Paediatric Oncology)
Metaplastic carcinoma of breast (MCB) is a rare breast malignancy. It is important to differentiate metaplastic carcinoma from malignant phyllodes and primary breast sarcomas because of their differing biological behavior and prognosis. We report four cases of MCB diagnosed over the past 15 years. Retrospective review of patient records in a tertiary care setting to retrieve cases diagnosed as MCB. Patient records of the past 15 years (2002–2015) were retrieved. Four histopathologically diagnosed cases of metaplastic carcinoma out of a total of 880 archived cases of breast carcinoma were studied along with their cytopathology. Immunohistochemistry was performed on sections. MCB comprised 0.45% of all breast malignancies. The four cases of MCB included MCB with chondroid metaplasia, spindle cell carcinoma, adenosquamous carcinoma, and carcinosarcoma. All the tumors were invariably triple negative (estrogen receptor, progesterone receptor, and Her2/Neu negative) and expression of other epithelial and mesenchymal markers was variable. MCB is a rare breast malignancy. Differential diagnosis is related to the presence of heterologous elements and degree of atypia seen in the lesion. It is important to be aware of this entity as it carries a poor prognosis.